Studies of Seed Germination in Four Rhododendron Species of Garhwal Himalayas - Razvi, Sajad; Prasad, Shailesh; Nautiyal, S. (Indian Forester, 2012)
Seed germination studies in four Rhododendron species were carried out in BOD incubator at 20°C ± 1°C temperature under continuous light as well as in open laboratory conditions at 25°C ± 2°C temperature. In BOD incubator, maximum 76.25% germination was recorded in the seeds of Rhododendron anthopogon followed by 61.5% in R. campanulatum and 59.25% in R. barbatum with 59.25% while minimum 53.5% was recorded in R. arboreum. However, in open lab conditions (25°C ± 2°C), maximum germination 56.5% was recorded in Rhododendron anthopogon followed by 47.5% in R. barbatumand minimum 41.0% in R. campanulatum. Highest number of seed per capsule was observed in R. campanulautum (900-1100) followed by R. arboreum (850-1000), R. barbatum (300-400) and R. anthopogon (350-450). Maximum seed length 2.93 mm and seed width 1 mm was observed in Rhododendron barbatum followed by R. campanulatum (2.04 and 0.63 mm) and R. arboreum (1.71 mm and 0.63 mm) while, minimum (1.04 mm and 0.47 mm) was recorded in R. anthopogon.